Use of Electrocardiography in Identification of Culprit Vessel and Localising the Lesion in Acute Myocardial Infarction with Angiographic Correlation (Global Journal of Medical Research, 2019)
Abstract not found
Keywords: acute myocardial infarction; electrocar- diogram; ST-segment elevation